2008
DOI: 10.1186/1471-2148-8-105
|View full text |Cite|
|
Sign up to set email alerts
|

GPR50 is the mammalian ortholog of Mel1c: Evidence of rapid evolution in mammals

Abstract: BackgroundThe melatonin receptor subfamily contains three members Mel1a, Mel1b and Mel1c, found in all vertebrates except for Mel1c which is found only in fish, Xenopus species and the chicken. Another receptor, the melatonin related receptor known as GPR50, found exclusively in mammals and later identified as a member of the melatonin receptor subfamily because of its identity to the three melatonin receptors despite its absence of affinity for melatonin. The aim of this study was to describe the evolutionary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(98 citation statements)
references
References 59 publications
5
89
0
4
Order By: Relevance
“…An in silico approach has suggested that GPR50 is the ortholog of the Mel 1C receptor (Dufourny et al, 2008). This conclusion is based on an analysis of the melatonin receptor family phylogenetic tree and the conserved synteny of genes surrounding the Mel 1C and GPR50 genes.…”
Section: B Gene Structure and Chromosomal Localizationmentioning
confidence: 99%
“…An in silico approach has suggested that GPR50 is the ortholog of the Mel 1C receptor (Dufourny et al, 2008). This conclusion is based on an analysis of the melatonin receptor family phylogenetic tree and the conserved synteny of genes surrounding the Mel 1C and GPR50 genes.…”
Section: B Gene Structure and Chromosomal Localizationmentioning
confidence: 99%
“…MT2 receptors may be the new target for development of hypnotic agents [2]. [31]. Its gene is located on the X chromosome (Xq28) and consists of 618 amino acids [4].…”
Section: Melatonin Receptorsmentioning
confidence: 99%
“…Rich Ser and 2 repeats (RA and SVHFK) were also found in the CTD (Figure 2). Dufourny et al (2008) analyzed the CTD by using a bidimensional Hydrophobic Cluster Analysis. They first aligned the repeated heptapeptide and found a heptad in the C-terminal extension of human GPR50.…”
Section: Discussionmentioning
confidence: 99%
“…GPR50 is a GPCR recently demonstrated to play an important role in adaptive thermogenesis in response to calorie intake (Levoye et al, 2006). Interestingly, a recent phylogenetic study of GPR50 and the melatonin receptors suggested that GPR50 was the mammalian ortholog of Mel1c (Dufourny et al, 2008); however, the receptor has experienced a number of changes throughout its evolution, including the mutation of numerous amino acids and the addition of a long C-terminal domain (CTD).…”
Section: Introductionmentioning
confidence: 99%